Copper alloy-nodular cast iron bimetallic wear-resisting and friction-reducing component and preparation method thereof
Through laser additive manufacturing technology, copper alloy is stacked on the surface of ductile iron and ultrasonic rolling treatment is carried out, the stability problem of copper alloy-steel bimetallic components under high pressure and high speed conditions is solved, and the excellent wear resistance and friction reduction performance of copper alloy-ductile iron bimetallic components are achieved.
Patent Information
- Application Number
- CN202510220363.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-27
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-02-27
AI Technical Summary
Under high pressure, high speed and complex working conditions, the steel matrix of copper alloy-steel bimetallic components is insufficient in impact resistance and dimensional stability, resulting in inaccurate contact surface coordination, reducing sealing performance, and thus causing hydraulic system failure.
Laser additive manufacturing technology is used to stack copper alloy layer by layer on the surface of ductile cast iron to form a copper alloy wear-resistant friction-reducing layer, and the bonding strength and wear resistance of the copper alloy layer are improved through ultrasonic rolling treatment.
The microhardness reaches 111.6-175.3HV, and the dry friction coefficient is 0.11-0.34. The copper alloy-ductile iron bimetallic parts have excellent wear resistance and friction reduction performance, which can meet the needs of the friction pair of the high-pressure plunger pump.
Smart Images

Figure CN119703117A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of wear-resistant and friction-reducing components, and in particular relates to a copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component and a preparation method thereof. Background Art
[0002] In hydraulic systems such as high-pressure plunger pumps, friction pair components (such as plungers, sleeves, etc.) need to withstand the severe challenges of high loads, high speeds, and complex working conditions, which places extremely high demands on the wear resistance, friction reduction, fatigue resistance, and thermal stability of the materials. As the core component of the hydraulic system, the performance of the plunger pump directly determines the efficiency and reliability of the entire equipment. Therefore, how to improve the material properties of friction pair components, especially to ensure their stability under high pressure, high speed, and extreme working conditions, has become an important technical problem in the development of the hydraulic industry.
[0003] The friction pair components of the hydraulic system mostly adopt a copper alloy-steel bimetallic structure. Copper alloy is widely used in the contact surface of the friction pair due to its excellent wear resistance, friction reduction and corrosion resistance; steel is usually used as the base material due to its high strength and good impact resistance. At present, the processing technology of copper alloy-steel bimetallic components mainly includes fusion welding, gas welding, brazing, explosion welding, thermal spraying, solid diffusion welding, casting, mechanical inlay, vapor deposition and powder metallurgy sintering. Under normal working conditions of high pressure, low speed and small temperature change, copper alloy-steel bimetallic components can provide ideal wear resistance and friction reduction performance, meeting the application requirements of most hydraulic systems with low loads or relatively stable working environments; however, under long-term high loads, high pressure, high speeds and complex working conditions, the impact resistance and dimensional stability of the steel matrix are often insufficient, which may lead to misalignment between contact surfaces, reduce sealing performance, and further cause failures such as insufficient flow, low pressure of the pump body, overheating or jamming. In addition, flow vibration and pressure pulsation in the hydraulic system may cause the fixed components to loosen and induce resonance, thereby accelerating the damage of the hydraulic system, and in severe cases even affecting the performance and service life of the entire machine. In order to break through this bottleneck, the application of copper alloy-ductile iron bimetallic components has gradually become a focus of attention in the field of high-end hydraulic parts manufacturing. Ductile iron not only has high strength, high plasticity and excellent toughness, but also has excellent shock absorption and energy absorption capacity, wear resistance, heat resistance and corrosion resistance. Compared with steel, ductile iron shows higher stability and reliability under extreme working conditions such as high temperature, low temperature, impact and vibration. Using ductile iron instead of steel for friction pair components in plunger pump assemblies not only significantly improves the strength, wear resistance and shock absorption performance of the components, but also achieves the multiple advantages of weight reduction and noise reduction while maintaining high dimensional accuracy. The application of copper alloy-ductile iron bimetallic components not only improves the overall performance of the hydraulic system, but also reduces its operating and maintenance costs to a certain extent.
[0004] The manufacturing of copper alloy-ductile iron bimetallic components faces many technical difficulties. The main challenges come from the significant differences in the physical, chemical and mechanical properties of the two materials. Since copper alloy and ductile iron have obvious differences in expansion coefficient, melting temperature and fluidity, during hot working processes such as welding and casting, the connection between the two often has defects such as pores, cracks and hardened structure, which seriously affect the mechanical properties and long-term stability of the bimetallic components; in addition, the difference in expansion coefficient may induce thermal stress during the cooling process, thereby leading to the formation of interface cracks. Ductile iron is very easy to form hardened quenching structure during the cooling stage of hot working. The presence of this structure will further reduce the bonding strength of the composite layer, especially under high temperature or high pressure environment. If these defects are not effectively controlled, it may lead to the failure of copper alloy-ductile iron bimetallic components.
[0005] In view of the difficulties and defects in the above-mentioned manufacturing process, laser additive manufacturing technology, as a high-precision and high-efficiency manufacturing method, provides a feasible solution for the preparation of copper alloy-ductile iron bimetallic composite parts. Laser additive manufacturing technology has unique advantages such as one-time forming, moldless forming and high material utilization rate, and can flexibly meet the manufacturing needs of complex structural parts; by accurately designing the composition of copper alloy powder and optimizing additive manufacturing process parameters, laser additive manufacturing technology can achieve the regulation of the wear resistance, friction reduction and strength of the copper alloy layer. However, how to use laser additive manufacturing technology to overcome the performance differences between materials and ensure the stability and reliability of copper alloy-ductile iron bimetallic parts under extreme working conditions, so as to meet the use needs of hydraulic components, is still a key issue that needs to be solved urgently. Summary of the invention
[0006] The purpose of the embodiments of the present invention is to provide a method for preparing a copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component, aiming to solve the problems raised in the above-mentioned background technology.
[0007] The embodiment of the present invention is implemented as follows: a method for preparing a copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component comprises the following steps: Treat the surface of ductile iron and smooth the surface; The treated ductile iron is placed in a sealed cabin, the powder feeding speed of the wear-resistant and friction-reducing layer powder is adjusted to 5-8 g / min, and the ductile iron is heated to 150-200° C. through a preheating platform; wherein the wear-resistant and friction-reducing layer powder includes 6%-8% of the reinforcing phase powder by mass, and the rest is the copper alloy spherical powder; the reinforcing phase powder includes 13%-15% of the lanthanum hexaboride ceramic powder by mass, and the rest is the nickel-coated graphite powder; the copper alloy spherical powder includes the following raw materials by mass percentage: Cr 1%-1.5%, Ni 0.5%-1.2%, Zr 0.2%-0.4%, Si 0.1%-0.3%, Nb0.01%-0.02%, and the balance is Cu; Under the process parameters of laser power of 800-1000W, scanning speed of 6-8mm / s, defocus of 0, and overlap rate of 40%-50%, the copper alloy is deposited layer by layer on the surface of ductile iron by laser additive manufacturing technology to form a copper alloy wear-resistant and friction-reducing layer; The copper alloy layer is flattened and subjected to ultrasonic rolling treatment to obtain a copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component.
[0008] Preferably, the copper alloy spherical powder is prepared by a gas atomization method, and the particle size of the prepared copper alloy spherical powder is 50-150 μm and the bulk density is 4-4.5 g / cm 3 , fluidity is 17.0-18.0s / 50g.
[0009] Preferably, the particle size of the nickel-coated graphite powder is 50-150 μm, and the thickness of the nickel coating is 1-5 μm; the particle size of the lanthanum hexaboride ceramic powder is 150-300 nm; the preparation method of the reinforcement phase powder is: pouring the nickel-coated graphite powder and the lanthanum hexaboride ceramic powder into a vacuum ball mill and ball milling them so that the nickel-coated graphite powder and the lanthanum hexaboride ceramic powder are evenly mixed to obtain the reinforcement phase powder.
[0010] Preferably, the preparation method of the wear-resistant and friction-reducing layer powder is: pouring the copper alloy powder and the reinforcing phase powder into a vacuum ball mill for ball milling, sieving the ball-milled powder to control the powder particle size to 50-150 μm, and then vacuum drying the sieved powder.
[0011] Preferably, the step of stacking the copper alloy layer by layer on the surface of the ductile iron using the laser additive manufacturing technology is to stack 5-7 layers, and the thickness of the copper alloy wear-resistant and friction-reducing layer is 4-5 mm.
[0012] Preferably, the process parameters of the ultrasonic rolling treatment are: rolling speed 400-500 mm / min, step distance 0.1-0.3 mm, pressing amount 0.05-0.08 mm, static pressure 0.5-0.8 MPa, ultrasonic frequency 22-25 kHz.
[0013] Another object of an embodiment of the present invention is to provide a copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component, which is prepared by the above-mentioned preparation method.
[0014] A method for preparing a copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component provided by an embodiment of the present invention avoids the generation of white cast structure and cracks due to the rapid heating and cooling of ductile iron during laser additive manufacturing by preheating before welding. The microhardness of the copper alloy wear-resistant and friction-reducing layer prepared by laser additive technology can reach 111.6-175.3HV. GCr15 steel is selected as the grinding pair. The dry friction coefficient of the wear-resistant and friction-reducing layer on the surface of the copper alloy is measured to be 0.11-0.34. The copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component prepared by the preparation method of the embodiment of the present invention not only has excellent wear resistance and friction reduction performance, but also the copper alloy wear-resistant and friction-reducing layer has good bonding with the ductile iron matrix, which can meet the use requirements of the friction pair of the high-pressure plunger pump; The copper alloy-ductile iron bimetallic wear-resistant and friction-reducing components prepared using laser additive manufacturing technology have a high degree of customization potential and can flexibly meet the needs of complex structural parts. Through precise design and manufacturing, they can shorten the processing cycle and effectively reduce material consumption and manufacturing costs, opening up a new path for the widespread application of this technology in the industrial field. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a microstructure photograph of the copper alloy wear-resistant and friction-reducing layer in the copper alloy-ductile iron bimetal wear-resistant and friction-reducing component prepared in Example 6 of the present invention; Figure 2 A microstructure photograph of the copper alloy-ductile iron interface in the copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component prepared in Example 6 of the present invention; Figure 3 This is a dry friction coefficient curve of the copper alloy wear-resistant and friction-reducing layer in the copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component prepared in Example 6 of the present invention. DETAILED DESCRIPTION
[0016] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0017] The embodiment of the present invention takes into account that ductile iron has a high carbon content and is prone to whitening under the action of laser thermal cycles, thereby forming cracks at the interface. In order to avoid this phenomenon during the laser additive manufacturing process, the ductile iron is preheated to prevent the formation of white structure in the subsequent laser cladding. In addition, copper has a relatively weak absorption capacity for lasers. The embodiment of the present invention can significantly improve the laser absorption rate of the copper alloy and enhance its strength by adding elements such as Cr, Ni, Zr, Si, and Nb. However, the high solid solubility of these elements in copper will cause the thermal conductivity of the copper alloy to decrease. The nano-scale lanthanum hexaboride particles added in the embodiment of the present invention have a lower melting point and a smaller tendency to agglomerate in liquid copper. During the laser melting process, the lanthanum hexaboride particles will dissolve in the molten pool and play a role in refining the grains and enhancing the thermal conductivity of the copper alloy during the solidification process. In addition, the addition of nickel-coated graphite powder can further improve the friction and wear properties of the copper alloy. The metal nickel layer on its surface can prevent the graphite from being excessively decomposed under the action of laser heat, thereby avoiding the adverse effects of excessive carbon elements on the properties of the copper alloy. The copper alloy layer obtained by laser additive manufacturing exhibits cast structure characteristics, with a relatively loose structure and prone to defects such as pores, spheroidization and cracks. For this reason, the embodiment of the present invention performs ultrasonic rolling treatment on the copper alloy cladding layer manufactured by laser additive manufacturing. By introducing strong plastic deformation, the porosity can be reduced and the grains can be refined, thereby improving the service strength of the copper alloy surface.
[0018] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0019] Embodiment 1: A copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component, the preparation method of which comprises the following steps: (1) Preparation of copper alloy spherical powder: The copper alloy spherical powder is prepared by a gas atomization method. The copper alloy spherical powder contains the following elements in mass percentage (Wt%): Cr1-1.5%, Ni0.5-1.2%, Zr0.2-0.4%, Si0.1-0.3%, Nb0.01-0.02%, and the balance is Cu; the prepared copper alloy spherical powder needs to meet the following standards: particle size of 50-150μm, bulk density of 4-4.5g / cm 3 , fluidity is 17.0-18.0s / 50g; (2) Preparing reinforcing phase powder: pouring nickel-coated graphite powder and lanthanum hexaboride ceramic powder into a vacuum ball mill, and using the vacuum ball mill for 3 hours to make the two powders evenly mixed; by weight percentage (Wt%), the lanthanum hexaboride ceramic powder is 13-15%, and the rest is nickel-coated graphite powder, wherein the particle size of the nickel-coated graphite powder is 50-150 μm, the thickness of the nickel layer is 1-5 μm, and the particle size of the lanthanum hexaboride ceramic powder is 150-300 nm; (3) Preparation of wear-resistant and friction-reducing layer powder: Pour the copper alloy spherical powder and the reinforcing phase powder into a vacuum ball mill, where the reinforcing phase powder accounts for 6-8% by weight (Wt / %) and the rest is the copper alloy spherical powder. After vacuum ball milling for 3 hours, the mixed powder is screened to ensure that the particle size of the mixed powder is 50-150 μm. The screened mixed powder is placed in a vacuum drying oven and evacuated to a vacuum degree of 5×E -1 Pa, adjust the holding temperature to 70℃ and the holding time to 20min to make the mixed powder fully dry; (4) The surface of the ductile iron is mechanically and chemically treated to remove oil, oxides and smooth the plate surface, and then the ductile iron is placed in a closed cabin. A heating platform for preheating the ductile iron and a laser powder feeding head that can move freely in a rectangular coordinate system are placed in the cabin. Argon gas with a purity of 99.99% is filled into the cabin to prevent oxidation of the copper alloy during the laser additive process. (5) Laser additive manufacturing technology is realized by a powder feeding device and a fiber laser. The specific process is as follows: the wear-resistant and friction-reducing layer powder is poured into the powder bin of the powder feeding device, the powder feeding speed is adjusted to 8g / min, and the ductile iron is preheated using a preheating platform in a closed chamber. The preheating temperature is 200°C. Ductile iron is used as the substrate, and the copper alloy is deposited layer by layer on its surface using laser additive manufacturing technology. The laser additive manufacturing process parameters are as follows: laser power 1000W, scanning speed 8mm / s, defocus amount 0, and the laser focus and the powder focus of the powder feeding head are ensured to be the same point. Each layer of copper alloy is composed of parallel multi-pass laser additive manufacturing of copper alloy. The overlap rate of each laser is 50%, and the dwell time between each pass is 1min. The protective gas is argon with a purity of 99.99%, and the gas flow rate is 15L / min. Five layers of copper alloy are prepared layer by layer in the vertical direction by this process. The total thickness of the prepared copper alloy wear-resistant and friction-reducing layer is 4-5mm. (6) The copper alloy wear-resistant and friction-reducing layer on the surface of the ductile iron is mechanically polished and smoothed, and then ultrasonic rolling treatment is performed to finally form a copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component. The ultrasonic rolling parameters are rolling rate of 500 mm / min, step distance of 0.3 mm, reduction of 0.05 mm, static pressure of 0.5 MPa, and ultrasonic frequency of 25 kHz.
[0020] Comparative Example 1 is compared with Example 1, except that the wear-resistant and friction-reducing layer powder used is 100% copper alloy spherical powder, and other steps and parameters remain unchanged.
[0021] Performance Test: Based on the preparation method of Example 1, the added mass of nickel-coated graphite powder, lanthanum hexaboride ceramic powder and copper alloy spherical powder was adjusted, and other steps and parameters remained unchanged. Five groups of experiments were carried out to obtain Examples 2 to 6, and the hardness and friction coefficient of the copper alloy wear-resistant and friction-reducing layer of the prepared samples (GCr15 steel was selected as the grinding pair) were analyzed and compared with the hardness and friction coefficient of the copper alloy layer of the sample prepared in Comparative Example 1. The results are shown in Table 1: Table 1
[0022] The sample prepared in Example 6 was analyzed to obtain the microstructure photo of the copper alloy wear-resistant and friction-reducing layer. Figure 1 As shown, the microstructure photo of the copper alloy-ductile iron interface is as follows Figure 2 As shown, the dry friction coefficient curve of the copper alloy wear-resistant and friction-reducing layer is as follows Figure 3 As shown, according to Figure 1 and Figure 2 It can be seen that the copper alloy wear-resistant and friction-reducing layer has good bonding with the ductile iron matrix, without defects such as cracks and pores.
[0023] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component, characterized in that: The following steps are involved: Treat the surface of ductile iron and smooth the surface; The treated ductile iron is placed in a closed cabin, the powder feeding speed of the wear-resistant and friction-reducing layer powder is adjusted to 5-8 g / min, and the ductile iron is heated to 150-200° C. through a preheating platform; wherein the wear-resistant and friction-reducing layer powder includes 6%-8% of the reinforcing phase powder by mass, and the rest is the copper alloy spherical powder; the reinforcing phase powder includes 13%-15% of the lanthanum hexaboride ceramic powder by mass, and the rest is the nickel-coated graphite powder; the copper alloy spherical powder includes the following raw materials by mass percentage: Cr 1%-1.5%, Ni 0.5%-1.2%, Zr 0.2%-0.4%, Si 0.1%-0.3%, Nb 0.01%-0.02%, and the balance is Cu; Under the process parameters of laser power of 800-1000W, scanning speed of 6-8mm / s, defocus of 0, and overlap rate of 40%-50%, the copper alloy is deposited layer by layer on the surface of ductile iron by laser additive manufacturing technology to form a copper alloy wear-resistant and friction-reducing layer; The copper alloy wear-resistant and friction-reducing layer is flattened and subjected to ultrasonic rolling treatment to obtain a copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component.
2. The method for preparing the copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component according to claim 1, characterized in that: The copper alloy spherical powder is prepared by a gas atomization method. The particle size of the prepared copper alloy spherical powder is 50-150 μm and the bulk density is 4-4.5 g / cm 3 , fluidity is 17.0-18.0s / 50g.
3. The method for preparing the copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component according to claim 1, characterized in that: The particle size of the nickel-coated graphite powder is 50-150 μm, and the thickness of the nickel coating is 1-5 μm; the particle size of the lanthanum hexaboride ceramic powder is 150-300 nm; the preparation method of the reinforcement phase powder is: pouring the nickel-coated graphite powder and the lanthanum hexaboride ceramic powder into a vacuum ball mill and ball milling them, so that the nickel-coated graphite powder and the lanthanum hexaboride ceramic powder are evenly mixed to obtain the reinforcement phase powder.
4. The method for preparing the copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component according to claim 1, characterized in that: The preparation method of the wear-resistant and friction-reducing layer powder is as follows: pouring copper alloy powder and reinforcing phase powder into a vacuum ball mill for ball milling, sieving the ball-milled powder to control the powder particle size to be 50-150 μm, and then vacuum drying the sieved powder.
5. The method for preparing the copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component according to claim 1, characterized in that: The step of stacking copper alloy layer by layer on the surface of ductile iron using laser additive manufacturing technology is to stack 5-7 layers, and the thickness of the copper alloy wear-resistant and friction-reducing layer is 4-5 mm.
6. The method for preparing the copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component according to claim 1, characterized in that: The process parameters of the ultrasonic rolling treatment are: rolling speed 400-500 mm / min, step distance 0.1-0.3 mm, pressing amount 0.05-0.08 mm, static pressure 0.5-0.8 MPa, and ultrasonic frequency 22-25 kHz.
7. A copper alloy-ductile iron bimetallic wear-resistant and friction-reducing component, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.
Citation Information
Patent Citations
Preparation method of modified anti-friction, wear-resistant and corrosion-resistant nano-ceramic powder material for additive manufacturing
CN107500782A
Method for improving corrosion resistance and wear resistance of cast iron and cast iron material
CN114016020A
Method for ultrahigh-speed laser cladding of nodular cast iron shaft parts
CN115110076A
Copper alloy-nodular cast iron bimetallic wear-resistant antifriction plate and preparation method thereof
CN116288340A
Method of hardfacing a part
US20140001161A1